EMERGING ANTIMICROBIAL RESISTANCE IN COMPANION, FARM ANIMALS AND POULTRY: A VETERINARY CONCERN (Journal of Medical & Health Sciences Review, 2025)
Antimicrobial resistance (AMR) development in companion, farm animals and poultry represents a vital worldwide problem because it threatens veterinary medicine alongside public health and threatens food security. Accumulated resistant bacterial strains in both livestock production and pet healthcare are primarily caused by overusing antibiotics thus making traditional antibiotic treatments less effective. The global AMR crisis worsens because zoonotic transmission of resistant pathogens between animals and humans makes the problem more complex. Poultry sector is one of the most intensive livestock sectors and a major reservoir for emergent and dispersal of antimicrobial resistant bacteria. Because of the widespread use of antibiotics in poultry for therapeutic, metaphylactic, prophylactic, and growth promoting purposes, selective pressures have been created which support MDR pathogens. Significant concerns related to zoonotic transmission through food and environmental routes make these resistant strains not only veterinary problems, but also public health risks. This review evaluates the complete set of factors responsible for animal antibiotic resistance through antibiotic distributions for therapeutic measures and disease prevention as well as their use for animal growth promotion. The study provides extensive analysis of the most problematic resistant bacterial species including Escherichia coli and Salmonella spp. Staphylococcus aureus and Enterococcus spp. which investigates their resistance mechanisms through horizontal gene transfer and efflux pumps and enzymatic antibiotic degradation mechanisms. Through scientific review of modern research and policy progress, this paper demonstrates the critical importance of combating AMR in companion and farm animals by implementing sustainable science-backed interventions for preventing pathogen resistance spread.